Cooperative Management Innovation as a Strategy to Encourage the Competitiveness of MSMES: Analyzing Challenges and Opportunities in the Digital Era : (Case Study of KSP Nasari Medan) - Wicaksono, M. Fadli; Meha, Nurmala Lutfi; Lestari, Yara; Chairane, Chairane; Hayati, Fitri (LPPPIPublishing, 2024)
This study aims to analyze cooperative management innovations as a strategy to increase the competitiveness of MSMEs in facing the digital era, with a case study at KSP Nasari Medan. The method used in this study is a descriptive case study, which describes and analyzes the implementation of management innovations at KSP Nasari as well as the challenges and opportunities faced by its member MSMEs in transforming to the digital world. Data collection was carried out through in-depth interviews with cooperative administrators and members, as well as observation of programs implemented by cooperatives. The results of the study show that KSP Nasari has identified various challenges faced by its member MSMEs, such as limited digital knowledge, inadequate infrastructure, and difficulties in accessing the digital market. To address this, cooperatives are implementing various management innovations, including digital skills training and increased access to technology. KSP Nasari also leverages collaboration with the government, the private sector, and educational institutions to support the development of MSMEs. However, obstacles in digital transformation still exist, especially related to infrastructure limitations and costs. The conclusion of this study is that cooperative management innovations, such as digital training and external collaboration, play an important role in strengthening the competitiveness of MSMEs. A more integrated and sustainable follow-up strategy is needed to support the development of MSMEs in the digital era. The suggestion of this research is to strengthen digital training programs, improve infrastructure, and expand cooperation with various related parties.